Community mental health: the importance of mental health - Rani Nur Umah; Intan Ramadayanti; Rina Rosdiana; Maha Putra (JOURNAL INCLUSIVE SOCIETY COMMUNITY SERVIES, 2024)
Attention to mental health is now increasing because it is very important in human life. Unfortunately, many people are less aware of or even underestimate mental health, even though mental health is as important as physical health. This is caused by a lack of understanding and knowledge about the importance of mental health. This condition can be experienced by anyone, including people in surrounding villages. The opportunities given by the village community for students to carry out community service activities motivate students to provide outreach about the importance of mental health. The method used in this activity is lecture and discussion using PowerPoint presentations regarding mental health material. This activity aims to increase public knowledge and understanding regarding mental health. It is hoped that the results of this socialization will make people more familiar with and understand the importance of mental health. With good understanding, people are expected to be able to live a balanced life with maintained physical and mental health